Analisis Rasio Keuangan untuk Mengukur Kinerja Keuangan pada Perusahaan CV. 3 KOM Periode Tahun 2008 - 2012 - Efri Amalia; Teguh Setiawan (Jurnal Ilmiah Aset, 2013)
The purpose of this study was to analyze the financial statements in an effort to assess the financial performance of CV. 3 Kom in the period 2008-2012 by using the liquidity ratio which is represented by current ratio, Leverage Ratio Debt or Debt Ratio (Debt to Total Assets Ratio), the activity represented by the Receivables Turnover Ratio, and profitability which is represented by Gross Profit margin. The population in this study was a case study in this research so that the population did not exist. This study did not use sampling techniques for it was a case study research. The results of the liquidity ratio showed the average of 3.53 over the standard company. Leverage ratio showed the average of 0.28 below standard of company. Activity ratios indicated averagebelow the average of 1.8 times below company’s standard, and Profitability ratios showed the average of 0.62 over the standard companies.